Early Mississippian sandy siltstones preserve rare vertebrate fossils in seasonal flooding episodes. Issue 6 (20th May 2016) - Bennett, Carys E.; Kearsey, Timothy I.; Davies, Sarah J.; Millward, David; Clack, Jennifer A.; Smithson, Timothy R.; Marshall, John E. A.
Abstract: Flood‐generated sandy siltstones are under‐recognised deposits that preserve key vertebrate (actinopterygians, rhizodonts, and rarer lungfish, chondrichthyans and tetrapods), invertebrate and plant fossils. Recorded for the first time from the lower Mississippian Ballagan Formation of Scotland, more than 140 beds occur throughout a 490 m thick core succession characterised by fluvial sandstones, palaeosols, siltstones, dolostone 'cementstones' and gypsum from a coastal–alluvial plain setting. Sandy siltstones are described as a unique taphofacies of the Ballagan Formation (Scotland, UK); they are matrix‐supported siltstones with millimetre‐sized siltstone and very fine sandstone lithic clasts. Common bioclasts include plants and megaspores, fish, ostracods, eurypterids and bivalves. Fossils have a high degree of articulation compared with those found in other fossil‐bearing deposits, such as conglomerate lags at the base of fluvial channel sandstones. Bed thickness and distribution varies throughout the formation, with no stratigraphic trend. The matrix sediment and clasts are sourced from the reworking of floodplain sediments including desiccated surfaces and palaeosols. Secondary pedogenic modification affects 30% of the sandy siltstone beds and most (71%) overlie palaeosols or desiccation cracks. Sandy siltstones are interpreted as cohesive debris flow deposits that originated by the overbank flooding of rivers and due to localised floodplain sediment transport at times of high rainfall; their association with palaeosols and desiccation cracks indicates seasonally wet to dry cycles throughout the Tournaisian. Tetrapod and fish fossils derived from floodplain lakes and land surfaces are concentrated by local erosion and reworking, and are preserved by deposition into temporary lakes on the floodplain; their distribution indicates a local origin, with sediment transported across the floodplain in seasonal rainfall episodes. These deposits are significant new sites that can be explored for the preservation of rare non‐marine fossil material and provide unique insights into the evolution of early terrestrial ecosystems.